1973
DOI: 10.1002/j.1537-2197.1973.tb07591.x
|View full text |Cite
|
Sign up to set email alerts
|

The Release Mechanism and Locomotor Behavior of Equisetum Sperm

Abstract: When antheridia of gametophytes of Equisetum hyemale L. are placed in water, only spermatid cells are released. These spermatid cells have from 6–12 fibrils radiating from 2–4 loci on the cell wall. One sperm is released from each spermatid cell. With high speed cinemicrography, it can be shown that sperm flagella beat three dimensionally with a continuous, traveling helical wave. A flagellar beat cycle is completed every 0.03 sec. In water the sperm swim rapidly at a rate of 300 μ per sec and traverse a helic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

1974
1974
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…The sperm of Pteridium aquilinum and Athyrium nipponicum (pteridophytes) move forward by ciliary beat of flagella (Wolniak and Cande 1980;Inouye and Hori 1991). The multiflagellate sperm of Equisetum hyemale change swimming direction by reverse gyration of all flagella (Bilderback et al 1973), which was not observed in L. japonicum in this study. High-speed video microscopy of the biflagellate sperm of Marchantia polymorpha (bryophyte) revealed that they do not show backward swimming (Miyamura et al 2002).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The sperm of Pteridium aquilinum and Athyrium nipponicum (pteridophytes) move forward by ciliary beat of flagella (Wolniak and Cande 1980;Inouye and Hori 1991). The multiflagellate sperm of Equisetum hyemale change swimming direction by reverse gyration of all flagella (Bilderback et al 1973), which was not observed in L. japonicum in this study. High-speed video microscopy of the biflagellate sperm of Marchantia polymorpha (bryophyte) revealed that they do not show backward swimming (Miyamura et al 2002).…”
Section: Discussioncontrasting
confidence: 51%
“…Three distinct swimming modes, rotation, swing, and forward-movement trailing spiral course have been reported in sperm of a liverwort Riccardia pinguis (Showalter 1926), several pteridophyte genera (Yuasa 1933b(Yuasa , 1933cBilderback et al 1973Bilderback et al , 1974, cycads (Norstog 1975) and Ginkgo biloba (Ridge et al 1997). The swimming of these sperm cells is quite different from the swimming mode of the well-known breaststroke in the forward and backward swimming in the Chlorophyta such as Chlamydomonas reinhardtii (Ringo 1967;Hyams and Borisy 1978).…”
Section: Introductionmentioning
confidence: 95%
“…Basal bodies overlie the MLS along the anterior coils and are roughly lined up in parallel with spline MTs; their constituent axonemes are directed slightly obliquely toward the cell posterior. This alignment establishes the direction of motility (Bilderback et al, 1973). In addition, the wide spline (150 -300 MTs) ensheaths the nucleus (except in Marsilea) and is involved in separation of cellular coils.…”
Section: Discussionmentioning
confidence: 86%
“…Comparisons among Equisetum, Psilotum and leptosporangiate ferns uncover common behavioural and structural features of their spermatozoids. In these cells, the longitudinal axis of the coils (a line running down the centre of the coils) is parallel, to the direction in which the cells swim (Bilderback et al, 1973). In contrast, the direction of movement in bryophytes and Selaginella gametes is perpendicular to the longitudinal axis of the coils.…”
Section: Discussionmentioning
confidence: 99%
“…Equisetum (vascular plant) 600 Bilderback et al (1973) Myzostomum (polychaete) 800 Ishijima et al (1994) Arenicola (polychaete) 340 Pasey et al (1994) Turritella (marine snail) (swimming forward) 900 Ishijima et al (1999) Corbicula (clam) 1200 Howard et al (2004) Psammechinus (sea urchin) 900 Gray and Hancock (1955) Lytechinus (sea urchin) 900 Brokaw (1972) Tripneustes (sea urchin) 1000 Gibbons (1980Gibbons ( , 1982 Bacillus (arthropod) Baccetti et al (1973a) Short wave 800…”
Section: Sperm Flagellamentioning
confidence: 99%